Tensions and synergies in arts‐integrated data literacy instruction: Reflections on four classroom implementations. (13th July 2022) - Matuk, Camillia; DesPortes, Kayla; Amato, Anna; Vacca, Ralph; Silander, Megan; Woods, Peter J.; Tes, Marian
Abstract: Data‐art inquiry is an arts‐integrated approach to data literacy learning that reflects the multidisciplinary nature of data literacy not often taught in school contexts. By layering critical reflection over conventional data inquiry processes, and by supporting creative expression about data, data‐art inquiry can support students' informal inference‐making by revealing the role of context in shaping the meaning of data, and encouraging consideration of the personal and social relevance of data. Data‐art inquiry additionally creates alternative entry points into data literacy by building on learners' non‐STEM interests. Supported by technology, it can provide accessible tools for students to reflect on and communicate about data in ways that can impact broader audiences. However, data‐art inquiry instruction faces many barriers to classroom implementation, particularly given the tendency for schools to structure learning with disciplinary silos, and to unequally prioritize mathematics and the arts. To explore the potential of data‐art inquiry in classroom contexts, we partnered with arts and mathematics teachers to co‐design and implement data‐art inquiry units. We implemented the units in four school contexts that differed in terms of the student population served, their curriculum priorities, and their technology infrastructure. We reflect on participant interviews, written reflections, and classroom data, to identify synergies and tensions between data literacy, technology, and the arts. Our findings highlight how contexts of implementation shape the possibilities and limitations for data‐art inquiry learning. To take full advantage of the potential for data‐art inquiry, curriculum design should account for and build on the opportunities and constraints of classroom contexts. Practitioner notes What is already known about this topic Arts‐integrated instruction has underexplored potential for promoting students' data literacy, including their appreciation for the role of context and real‐world implications of data and for the personal and social relevance of data. Arts‐integrated instruction is difficult to implement in school contexts that are constrained by disciplinary silos. What this paper adds Descriptions of four data‐art inquiry units, which take an arts‐integrated approach to data literacy. Examples of the synergies and tensions observed between data literacy, technology, and the arts during classroom implementation in four different schools. Reflections on the role of school contexts in shaping disciplinary synergies and tensions. Implications for practice and/or policy Arts‐integration offers opportunities for data literacy learning. Consideration of the unique resources and constraints of classroom contexts is critical for fulfilling the promises of data‐art inquiry learning. There is a need to develop school support specific to arts‐integrated data literacy instruction.